2021
DOI: 10.1016/j.eclinm.2021.100964
|View full text |Cite
|
Sign up to set email alerts
|

The association of a novel digital tool for assessment of early childhood cognitive development, ‘DEvelopmental assessment on an E-Platform (DEEP)’, with growth in rural India: A proof of concept study

Abstract: Background There is an urgent need to fill the gap of scalable cognitive assessment tools for preschool children to enable identification of children at-risk of sub-optimal development and to support their timely referral into interventions. We present the associations between growth in early childhood, a well-established marker of cognitive development, and scores on a novel digital cognitive assessment tool called DEvelopmental Assessment on an E-Platform (DEEP) on a sample of 3-year old pre-sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…DEEP metrics have been demonstrated to be predictive of a child’s BSID-III cognitive score using a supervised machine learning analysis approach 41 . DEEP scores in this sample show significant positive associations with concurrently and prospectively measured HAZ 42 , which is one of the most commonly used proxy indicators of cognition 43 , 44 . DEEP scores were scaled to z-scores to allow comparison of the effects of cumulative adversities on physical growth versus cognition.…”
Section: Methodsmentioning
confidence: 74%
“…DEEP metrics have been demonstrated to be predictive of a child’s BSID-III cognitive score using a supervised machine learning analysis approach 41 . DEEP scores in this sample show significant positive associations with concurrently and prospectively measured HAZ 42 , which is one of the most commonly used proxy indicators of cognition 43 , 44 . DEEP scores were scaled to z-scores to allow comparison of the effects of cumulative adversities on physical growth versus cognition.…”
Section: Methodsmentioning
confidence: 74%
“…In Early Childhood Care and Education (ECCE), this shift is pivotal as it shapes the cognitive development of young learners. (Bhavnani et al, 2021;Hasanah et al, 2023;Iis et al, 2022;Shaharudin et al, 2020). The importance of managerial competency among administrators in the field of ECCE is becoming increasingly significant as the digital age continues to advance (Musa et al, 2020(Musa et al, , 2022.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the home environment plays a signi cant role in shaping children's development by providing them with learning opportunities facilitated by parents (8). Simple activities such as reading stories, having books (9), and playing (9)(10)(11) can have positive effects on children's early development, thanks to their parents. Nonetheless, research has shown that there is a lack of participation and family support when it comes to promoting the early development of children (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Mobile health (mhealth) is currently being used to enhance collaboration (18), improve communication, and optimize care processes between healthcare providers and patients (19,20). Research has shown that m-health interventions have a positive impact on certain aspects of children's development, such as cognitive and physical growth (10,21), overcoming geographical barriers, addressing the shortage of specialized staff, and facilitating cognitive assessments (22).…”
Section: Introductionmentioning
confidence: 99%